Growing a CdS flag from a wire with in situ control of the catalyst. Issue 20 (5th May 2021) - Dai, Beibei; Fan, Chao; Xu, Xing; Qi, Zhuodong; Xiao, Qin; Wei, Jinhui; Jiang, Sha; Zhang, Qinglin
Abstract : The controllable growth of a flag-like CdS microstructure from a wire is realized by in situ manipulation of the catalyst. Abstract : Flag-like CdS microstructures were achieved via a physical vapor deposition (PVD) route. A CdS flag was grown from a wire by changing, in situ, the position of the Pb catalyst from the tip to the sidewall of the wire, which was achieved by controlling the radius of a Pb droplet in the growth process to break the Nebol'sin inequality criteria. The microstructure characterization further reveals that the growth of the flag is assisted by the template of the CdS wire sidewall. By investigating the morphology evolution of the sample at different growth stages, the growth mechanism is well understood. Additionally, the power-dependent photoluminescence (PL) shows that the CdS flag possesses a higher defect density than the CdS wire, which may result in the wider optoelectronic response range of the former compared to the latter.